2021
DOI: 10.1155/2021/6811373
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pulmonary Rehabilitation on Respiratory Functions, and the Quality of Life, following Coronary Artery Bypass Grafting: A Randomised Controlled Study

Abstract: Objective. Examining the effects of a pulmonary rehabilitation (PR) program applied to patients undergoing coronary artery bypass grafting (CABG) surgery with open heart technique on respiratory functions, functional capacity, and quality of life (QoL). Design. This randomised controlled study applied the Consolidated Standards of Reporting Trials statement. Methods. The study was conducted with two groups: the intervention group ( n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The initial search found a total number of 2036 relevant articles from the previously mentioned four search engines. The initial title and abstract screening isolated 62 articles, and full-text screening was reduced to 9 relevant articles [ 32 , 33 , 34 , 38 , 39 , 40 , 41 , 42 , 43 ]. The articles found through hand search were not included in the final analysis due to further inappropriateness with the protocol ( Supplementary Method 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial search found a total number of 2036 relevant articles from the previously mentioned four search engines. The initial title and abstract screening isolated 62 articles, and full-text screening was reduced to 9 relevant articles [ 32 , 33 , 34 , 38 , 39 , 40 , 41 , 42 , 43 ]. The articles found through hand search were not included in the final analysis due to further inappropriateness with the protocol ( Supplementary Method 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We reported detailed findings of the included studies (Table 1 , Ref. [ 32 , 33 , 34 , 38 , 39 , 40 , 41 , 42 , 43 ]).…”
Section: Resultsmentioning
confidence: 99%
“…A small exploratory study showed that adding a home-based rehabilitation program for older patients undergoing CABG or valve surgery may enhance their functional status and decrease the duration of hospitalization [ 33 ]. Patients who have had CABG recover more quickly when they receive pulmonary and cardiac rehabilitation programs, and they may have better heart function and quality of life after cardiac rehabilitation [ 34 , 35 ]. Therefore, avoiding postoperative complications is crucial for a better quality of life since these complications are nightmares and frightening to patients and may risk their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significant progress made in the field of anesthetics, cardiopulmonary bypass operations, and pre-and postoperative care, CABG remains linked to a notable incidence of pulmonary complications [PPC] [10] . In the preoperative and postoperative care of patients after heart surgery, the use of pulmonary physiotherapy has considerable significance in addressing pulmonary complications, enhancing patient prognosis, and contributing to overall treatment efficacy [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Girgin et al [11] applied pulmonary rehabilitation to patients undergoing CABG for four days post-operative, helping them recover their functional capacity faster.…”
Section: Discussionmentioning
confidence: 99%